Basic Theories of Geopolitics (Czech Journal of International Relations, 1994)
To some, the question mark associated with the title of this chapter may seem unnecessary. After all, the very concept of geopolitics clearly and comprehensibly expresses the relationship between political phenomena and processes on the one hand and geographical space on the other. Still, there is a question mark here. Perhaps no other term in political science has become as discussed as "geopolitics".It wasn't always like that. At the time when the term "geopolitics" was first used by a Swedish researcher R. Kjellen in 1899, the scientific field of political geography was already taking shape, under whose founder the German geographer Friedrich Ratzel, who wrote the work Politische 1 in 1897, is considered Geography. Both terms are then used together, and above all the important personalities of political geography of the first half of the 20th century were also considered significant theorists in geopolitics.A very important theoretical geopolitical school arose in the interwar period in Germany. And it was precisely this fact that caused the very term "geopolitics" to be condemned after the Second World War and even used as a label for "non-scientific" political geography. The German geopolitical school was accused of theoretically preparing the territorial conquests of Nazi Germany.